THU0215 Effects of tofacitinib on patient-reported outcomes in a phase 3 study of chinese patients with active rheumatoid arthritis and an inadequate response to dmards. (15th June 2017) - Li, Z; An, Y; Li, G; Wang, L; Kwok, K; Wu, Q; ,
Abstract : Background: Rheumatoid arthritis (RA) worsens patients' health-related quality of life. 1 Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of RA. Improvements in patient-reported outcomes (PROs) have been reported in the global population of Phase 3 tofacitinib trials. 2 Objectives: To explore the effect of tofacitinib administered with conventional synthetic DMARDs (csDMARDs) on PROs in Chinese patients with RA and an inadequate response to DMARDs. Methods: This was a post-hoc analysis of data from Chinese patients in the 12 month, double-blind Phase 3 study ORAL Sync (NCT00856544 ), with patients randomised 4:4:1:1 to tofacitinib 5 mg BID, tofacitinib 10 mg BID, placebo (PBO)→tofacitinib 5 mg BID or PBO→tofacitinib 10 mg BID, with csDMARDs. Non-responders (defined as those who did not achieve a 20% improvement in both of the swollen or tender joint counts) receiving PBO advanced blindly to tofacitinib at Month 3; all remaining PBO patients advanced to tofacitinib at Month 6. Least squares mean changes from baseline were reported for Health Assessment Questionnaire-Disability Index (HAQ-DI), patient assessment of arthritis pain (VAS), patient global assessment of disease activity (PtGA), Functional Assessment of Chronic Illness Therapy (FACIT) Fatigue scale, Short Form-36 Health Survey (SF-36), EuroQol five dimensions questionnaire (EQ-5D), and Work Limitations Questionnaire (WLQ), using a mixed-effects model for repeated measures. All patients receiving ≥1 dose of study treatment with ≥1 post-baseline assessment were included. Results: Overall 216 patients were included (n=86, tofacitinib 5 mg BID; n=86, tofacitinib 10 mg BID; n=22, PBO→tofacitinib 5 mg BID; n=22, PBO→tofacitinib 10 mg BID). There were no major differences in demographics or baseline characteristics between treatment groups. At Month 3, tofacitinib resulted in significantly greater changes in HAQ-DI (5 mg BID, p<0.05; 10 mg BID, p<0.001), PtGA (5 mg BID, p<0.05; 10 mg BID, p<0.001), Pain (5 mg BID, p<0.001; 10 mg BID, p<0.001) and SF-36 Physical Component Summary (PCS) scores (5 mg BID, p<0.05; 10 mg BID, p<0.001) vs PBO (Figure). Numeric improvements in FACIT-Fatigue, SF-36 Mental Component Summary (MCS) [Figure] and EQ-5D health state profile (utility scores) were observed at Month 3 with tofacitinib vs PBO. There were no improvements in WLQ observed at Month 3 with tofacitinib vs PBO. Improvements were generally maintained at 6 and 12 months (Figure). The proportion of patients achieving HAQ-DI improvement ≥0.22 from baseline at Month 3 was significantly higher with tofacitinib vs PBO (5 mg BID, p<0.05; 10 mg BID, p<0.05). Conclusions: Tofacitinib 5 and 10 mg BID administered with csDMARDs significantly improved PROs including SF-36 PCS, PtGA, physical function and pain vs PBO. These improvements were maintained for up to 12 months in Chinese patients with RA. References: Strand V, Khanna D. Clin Exp Rheumatol 2010; 28: S32-S40. Strand V et al. Arthritis Care Res (Hoboken) 2016. doi:10.1002/acr.23004. Acknowledgements: This study was sponsored by Pfizer Inc. Editorial support was provided by C Evans of CMC and was funded by Pfizer Inc. Disclosure of Interest: Z. Li Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Y. An Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, G. Li Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Q. Wu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc